The Change of Identity and Memory on Urban Space with Project Impact: Karaköy Kemeraltı District - Tepeli, Özlem; Ocakçı, Mehmet (ICONARCH International Congress of Architecture and Planning, 2017)
Historical cities enter into a process of metamorphosis with some applications to opposite their specific identity when the economic and cultural production and consumption is increasingly globalizing nowadays. Therefore, it becomes difficult to sustain urban identity and memory. The cities began to resemble each other by losing their own identity due to the interventions on urban spaces in recent times. Thus, the urban identity has become a major discussion matter. Especially the old city centers are seen as high potential areas for transformation due to their central location with the cities began to be perceived as a commodity. The old city centers play a central role in the marketing of city or re-branding campaign because of their economic potential. The cities can create new identity elements while preserving existing components on the other hand. It is important to add new components without losing their original identity at this point. Otherwise the continuity of the urban memory could be damaged. The collective memory created by the citizens is affected by the constructions as destructions. Therefore, it becomes important to detect the continuity of urban identity and memory which are continuously reproduced and changed with references from the past and the present. This study aims to scope the importance of perception of the different layers of the city in assessing the effects of the changes occurring in the urban space on urban identity and memory. With this approach, Karaköy Kemeraltı district is designated as a case study. The area had many changes since its very rich historical past and entered into a rapid process of change in recent times. Especially the planned Galataport Project has affected the area and old trading function began to transform the leisure and tourism sector. The case study consists of two stages as the spatial analysis and survey. The changes on urban pattern and functions of structures are put forward with spatial analysis such as pattern analysis, registration analysis and structure function analysis for 2008 and 2015 years.